“Losanga” decorated imitations of italic late republican black gloss tableware from South-Western Iberia: A multi-analytical/microchemical characterization - Schiavon, Nick (2019)
Themicro-chemical/mineralogical composition of samples of grey-paste imitations of Italic Late Republican black gloss tableware displaying a particular kind of lozenge-shaped decoration (“Losanga pottery”) from Portuguese and Spanish archaeological sites in SWIberia has been analysed by BSEM + EDS, μXRD, Powder XRD, Portable XRF and μRaman spectroscopy. “Losanga” decorated ceramics have been found throughout theWestern Mediterranean. Most of the sherds display a green-brown to greyish-black engobe at the surface resembling the gloss found in Attic pottery from Classical Greece. The overall chemical, mineralogical and fossiliferous homogeneities of the ceramic paste show common features (low K-feldspar/plagioclase ratio, high Ca content, abundance of well-preserved fragments of foraminifera microfossils) that indicate low firing conditions in the kiln ranging from 650 to 900 °C. With respect to the ceramic body, analytical results confirm an enrichment in the surface gloss layer of iron, potassium and aluminium and a depletion in silicon and calcium; the very fine grain size of the surface coating suggests elutriation of iron oxide-rich clays as confirmed by the presence of magnetite, maghemite and goethite in μ-XRD scan. Chemical and mineralogical data also suggest that the firing process was performed in a 600–850 °C temperature range, adopting the well-known technique of alternating oxidizing and reducing firing conditions largely employed at the time. The analytical results, while compatible with the archaeological hypothesis of a common provenance of the raw materials for pottery production from the Guadalquivir valley workshops cannot be considered conclusive due to the similarity in the geological substrate in the two SW Iberian regions under study.